2023
DOI: 10.1108/ijoa-10-2022-3442
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational politics, organizational disidentification and counterproductive work behaviour: moderating role of external crisis threats to work

Abstract: Purpose The purpose of this study is to unpack the relationship between employees’ perceptions of organizational politics and their counterproductive work behaviour, by postulating a mediating role of organizational disidentification and a moderating role of perceived external crisis threats to work. Design/methodology/approach The empirical assessment of the hypotheses relies on survey data collected among employees who work in a large banking organization. Findings Perceptions that organizational decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 99 publications
0
4
0
4
Order By: Relevance
“…Failure to do so may result in the organization's collapse as the consequences intensify over time (Riggio & Newstead, 2023). In addition, past research has found that organizational crises produce generalized negative emotions among corporate members (Ozcelik et al, 2020;Restubog et al, 2020), creating diverse implications for HR management (Carnevale & Hatak, 2020;Clercq & Pereira, 2023;Lloyd et al, 2020).…”
Section: Organizational Crisismentioning
confidence: 99%
See 3 more Smart Citations
“…Failure to do so may result in the organization's collapse as the consequences intensify over time (Riggio & Newstead, 2023). In addition, past research has found that organizational crises produce generalized negative emotions among corporate members (Ozcelik et al, 2020;Restubog et al, 2020), creating diverse implications for HR management (Carnevale & Hatak, 2020;Clercq & Pereira, 2023;Lloyd et al, 2020).…”
Section: Organizational Crisismentioning
confidence: 99%
“…Emotions are not just disruptive and maladaptive forces that impact human beings but antecedents of behavioral intentions that reduce the negative states and enhance the positive (Lazarus, 1993;Spector & Fox, 2002). Positive emotions are related to organizational citizenship behaviors, while negative emotions produce counter-productive work behaviors, poor performance, and high turnover (Beetz & Ozcelik, 2021;Clercq & Pereira, 2023;Greenidge & Coyne, 2014;Ozcelik et al, 2020). For instance, greater workplace loneliness drives negative emotions, which relate to less affective commitment to the organization and lower job performance (Ozcelik & Barsade, 2018;Sullivan & Bendell, in press).…”
Section: Emotions During Organizational Crisesmentioning
confidence: 99%
See 2 more Smart Citations
“…Não fazer isso pode resultar no colapso da organização, pois as consequências se intensificam com o tempo (Riggio & Newstead, 2023). Além disso, pesquisas anteriores descobriram que as crises organizacionais produzem emoções negativas generalizadas entre os membros corporativos (Ozcelik et al, 2020;Restubog et al, 2020), criando diversas implicações para a gestão de RH (Carnevale & Hatak, 2020;Clercq & Pereira, 2023;Lloyd et al, 2020).…”
Section: Crise Organizacionalunclassified